2021
DOI: 10.1097/brs.0000000000003938
|View full text |Cite
|
Sign up to set email alerts
|

Factors Considered in Ranking Spine Surgery Fellowship Applicants

Abstract: Study Design. Cross-sectional study. Objective. To determine which factors spine surgery fellowship program directors (PDs) consider most important when ranking applicants. Summary of Background Data. Spine surgery is a popular orthopedic subspecialty. As such, the spine fellowship match process is highly competitive. Surveys of fellowship PDs in orthopedic sports medicine and hand surgery have demonstrated differing opinions regarding factors considered most important when ranking fellowship applicants. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…This may have led fellowship programs to rely more heavily on letters of recommendation or personal phone calls as previous studies have shown the importance of personal connections in the match process. 10,16 Yong et al 17 assessed the perspectives of fellowship directors and applicants regarding the virtual interview process for orthopaedic surgery trauma fellowships. The authors found that 75% of fellowship directors stated that virtual interviews limited their ability to familiarize themselves with an applicant and only 50% reported that they were comfortable ranking an applicant after a virtual interview.…”
Section: Discussionmentioning
confidence: 99%
“…This may have led fellowship programs to rely more heavily on letters of recommendation or personal phone calls as previous studies have shown the importance of personal connections in the match process. 10,16 Yong et al 17 assessed the perspectives of fellowship directors and applicants regarding the virtual interview process for orthopaedic surgery trauma fellowships. The authors found that 75% of fellowship directors stated that virtual interviews limited their ability to familiarize themselves with an applicant and only 50% reported that they were comfortable ranking an applicant after a virtual interview.…”
Section: Discussionmentioning
confidence: 99%
“…Program directors were then asked to evaluate 12 specific factors that might be considered in ranking fellowship applicants based on prior surveys of orthopaedic fellowship program directors. [3][4][5][6] These 12 criteria were displayed in a random order for each survey recipient. Randomization was automated by the online survey tool used to distribute the survey (Qualtrics, Provo, UT).…”
Section: Methodsmentioning
confidence: 99%
“…This scoring system is consistent with surveys of program directors from orthopaedic trauma, spine, sports medicine, and hip and knee arthroplasty subspecialties. [3][4][5][6]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations